Peran Pembiayaan Bank Syariah Untuk Mendukung Kesejahteraan Usaha Mikro Kecil Dan Menengah Di Kecamatan Lembah Sorik Marapi: Syaiful Sori Pada - Syaiful Sori Pada (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2026)
Abstract The Role of Islamic Bank Financing to Support the Welfare of Micro, Small and Medium Enterprises in the Sorik Marapi Valley. This study aims to determine: 1) The role of Bank Syariah Indonesia financing to support the welfare of Micro, Small and Medium Enterprises in the Lembah Sorik Marapi District; 2) the role of BankSumut Syariah financing to support the welfare of Micro, Small and Medium Enterprises in the Lembah Sorik Marapi District. This study is a qualitative study, namely a research procedure that produces descriptive data in the form of words, pictures, and not numbers, from people or behavior that can be observed. The results of the study indicate that Islamic financing from Bank Syariah Indonesia has a significant positive impact on the development of Small and Medium Enterprises (SMEs) in the Lembah Sorik Marapi District. This financing is not only in accordance with sharia principles and avoids usury, but has also increased customer income substantially. Challenges faced by Islamic banks include limited collateral from customers, human resource issues, and lack of government support. Nevertheless, Islamic banks play an important role in providing capital and technical support to help SMEs grow and develop. This study shows that Islamic financing is an effective tool in improving the welfare of small and medium enterprises, with procedures that include in-depth feasibility assessments. Keywords: Islamic Financing, Economic Welfare, UMKM